Načela disciplinskega pristopa - Pšunder, Mateja (Sodobna pedagogika, 2006)
Research shows that discipline at school is still quite traditional and, as such, problematic as it does not stimulate the development of self-discipline and responsibility in pupils. In order to make discipline in schools topical, it must first be appropriately understood. Today, the prevailing conviction is that the quality or efficiency of disciplinary methods cannot be assessed by external experts, but only by teachers themselves. The purpose of the article is to bring together the viewpoints of certain contemporary authors about discipline, taking into account the results of researches into this issue in Slovenia and abroad, into the principles which are to lead teachers in their assessment of disciplinary methods. We employed the common points of individual authors as the starting points for formulating the principles. We believe that the principles oriented to the achievement of both basic goals of discipline could also be relevant in Slovenia.
Keywords: vzgoja in izobraževanje; disciplina; šolski red; raziskave